Dermoscopic Follow-Up of the Skin towards Acute Graft-versus-Host-Disease in Patients after Allogeneic Hematopoietic Stem Cell Transplantation. (30th June 2016) - Kaminska-Winciorek, Grazyna; Czerw, Tomasz; Kruzel, Tomasz; Giebel, Sebastian
Abstract : Background . Acute graft-versus-host disease (aGVHD) involving skin is one of the most frequent complications of allogeneic hematopoietic stem cell transplantation (alloHSCT), usually diagnosed based on clinical manifestations. So far, skin biopsy with histopathological evaluation is the only method to confirm the diagnosis. Objective . In this prospective study we monitored alloHSCT recipients by dermoscopy in order to assess its utility as an alternative noninvasive tool to early diagnose acute GVHD. Methods . Thirteen consecutive patients who received alloHSCT were examined clinically and dermoscopically towards aGVHD [days 28 (±7), 56 (±7), and 100 (±7)], as well as in each patient who developed cutaneous aGVHD diagnosed according to clinical criteria (Glucksberg scale). Results . Six patients (46%) developed symptoms of cutaneous acute GVHD (grade 1, n = 3 ; grade 2, n = 3 ). Dermoscopic evaluation revealed pinkish or reddish background and well-visible, multiple thin telangiectasias. Conclusion . To our knowledge, this is the first report on the use of dermoscopy to evaluate skin involvement in the course of acute GVHD suggesting its role as a diagnostic tool in follow-up of GVHD, which can be also used before clinical symptoms occur.